Consumo alimentar e construção identitária: atribuições de sentido do ponto de vista das classes populares em um contexto midiático - Portelinha, Maria Beatriz (2018)
The subject of this thesis is the meaning attributions to popular classes’ everyday food consumption. The consumption, as a social and cultural phenomenon, allows us to investigate society’s ways of life and the meaning attributions given by its members to everyday life. As food consumption, specifically, the meanings are constantly built and materialized into practices, whether due the physical needs or the desire of doing so. By associating food consumption to social classes, specific eating manners become noticeable within each social group having its own eating habitus, revealing traces of their social dynamic. The meanings attributed to consumption are built by the collective, in a way that the culture and socialization manners affect the individual’s ways of thinking, felling and acting, affecting also their lifestyle and their identity formation. The consumption preferences and taste, influenced by the habitus and the individual’s lifestyle, are objects of negotiation between individual’s perceptions and collective knowledge, as a negotiation between individual and society. From that, our aim in this study is to think the relations between food consumptions and the meanings built in its practices, investigating its relation with identity construction in a media society. We base our study in theories of authors who articulate the consumption to social relations as Bourdieu, Barros and Rocha, García Canclini, Martín-Barbero, Slater, Landowski, Barbosa and Fischler, to verify the meaning attributions about food consumption and how they are related to the everyday life of popular classes. By means of in-depth interviews with decision makers from families of those classes we investigated the eating consumption and media practices of those individuals, verifying how it relates to their lifestyles. Synthetically, we noticed that the eating consumption practices are related to the demands of their everyday practices and their cultural and social identities. The association between feeding and social class reveled different manners of food preparation, behavior, purchasing strategies and food preferences, with social condition stablishing itself as a category that guides their actions.